Faktor Faktor Yang Mempengaruhi Partisipasi Masyarakat Dalam Pemilihan Kepala Kampung Lempake Tahun 2021 Di Kecamatan Biatan Kabupaten Berau - Andi Riski Mulia Saputra; Budiman, Budiman; Dyastari, Letizia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This research aims to identify the factors influencing community participation in the election of the Village Head in Lempake in 2021 in the Biatan Subdistrict, Berau Regency. The study was conducted in the Biatan Lempake Village in the Biatan Subdistrict, Berau Regency. The research design used was qualitative descriptive. The research involved several stages, including field research through observation, interviews, and documentation as a supporting element for the study. The qualitative descriptive analysis involved examining the data obtained based on real-life situations and connecting them with theories that support the discussion. This approach allowed for an exploration of the cause-and-effect relationships influencing political participation in the village. The descriptive analysis included data collection, data presentation, data analysis, and, ultimately, drawing conclusions. The indicators in this study were categorized as follows: Due to Stimulus, Due to Individual Characteristics, Due to Social Characteristics, and Due to Situational and Environmental Factors. The research findings demonstrated that stimuli, individual characteristics, social characteristics, and situational/environmental factors influenced community participation in the village head election held in Lempake Village, Biatan Subdistrict, Berau Regency.